Analysis for Financial Management (Sách Photocopy) - Higgins Robert C (American : McGraw Hill/Irwin, 2004)
Analysis of Financial Management 7e is a paperback text and has been written to present standard techniques and modern developments in a practical and intuitive manner. It is intended for non-financial managers and business students interested in the practice of financial management. Emphasis is on the managerial applications of financial analysis.
Keywords: Quản lý tài chính-- Phân tích; Công ty kinh doanh--Tài chính